2022
DOI: 10.1039/d2cs00256f
|View full text |Cite|
|
Sign up to set email alerts
|

Polycatenanes: synthesis, characterization, and physical understanding

Abstract: Polycatenanes are a class of polymers that contain interlocked rings. This review explores the different polycatenane architectures with a focus on their synthesis, properties, simulation, and modelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 139 publications
0
33
0
Order By: Relevance
“…The threading occurs in diverse settings and concentration regimes. For example, in dilute regime, the threading can support topology-based supramolecular architectures, such as polycatenanes [7][8][9] or polyrotaxanes, with their movable threaded ring constituents, promising the development of complex synthetic molecular-sized machines. [10][11][12] In the biological realm, threading occurs across domains of life, typically at higher densities, from semidilute to melt conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The threading occurs in diverse settings and concentration regimes. For example, in dilute regime, the threading can support topology-based supramolecular architectures, such as polycatenanes [7][8][9] or polyrotaxanes, with their movable threaded ring constituents, promising the development of complex synthetic molecular-sized machines. [10][11][12] In the biological realm, threading occurs across domains of life, typically at higher densities, from semidilute to melt conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, different models have shown that, at small scales, the Rouse-like relaxation modes seen in linear polymers are replaced by slower ones in mechanically bonded chains of rings. 11,15,23,24 These ongoing efforts have significantly advanced our understanding of isolated and interacting catenanes in bulk. 15,16,22−27 However, except for Hopf links, 28,29 no characterization exists yet of catenanes in spatial confinement, despite it being a natural avenue considering the body of knowledge available for conventional polymers in channels and slits.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recent breakthroughs in the synthesis of linear catenanes, , supramolecular structures made of a linear succession of mechanically bonded rings, have boosted interest for their applicative potential, ranging from molecular recognition and catalysis to materials science, as well as for understanding their unique properties, especially those afforded by mechanical bonding. …”
Section: Introductionmentioning
confidence: 99%
“…However, to study and fully utilize these materials, synthetic protocols to access specic MIP architectures need to be developed. For some MIP architectures, such as polycatenanes, [16][17][18] the synthetic obstacles are particularly pronounced: the yields of ring closing reactions (required in the synthesis of a catenane) toward a specic macrocycle are generally not high yielding. 19 Furthermore, ring formation is favoured at low monomer concentrations, while higher reaction concentrations are generally required to access high molar mass polymers.…”
Section: Introductionmentioning
confidence: 99%